Rock and paleomagnetic results of sediments from the Tenchong Qinghai Lake, Yunnan province, China - Tingwei Zhang; Xiaoqiang Yang; Chenglong Deng (PANGAEA, 2025)
We present results of corrected degree of anisotropy susceptibility (Pj), χARM/SIRM ratio, isothermal remanent magnetization (IRM) component analysis and First-order reversal curves (FORC) principal component analysis of the sediment from Tenchong Qinghai Lake. This lake is located in the Tengchong district, Yunan province of China (25°08'06'' - 25°07'44''N, 98°34'11'' - 98°34'26''E). The age-depth model of cores was reconstructed by Yang et al (2022). The anisotropy susceptibility data was measured by using a Kappabridge MFK1-FA. The SIRM and anhysteretic remanent magnetization (ARM) data are obtained from Yang et al (2022), and the χARM/SIRM ratio was calculated. IRM acquisition curves was measured using a vibrating sample magnetometer (VSM, princeton MicroMag 3900). All IRM acquisition curves were decomposed into magnetic components using the method described in Maxbauer et al. (2016). All the FORC data was processed using the FORCinel software (version 3.08) with smoothing factors of Sc0=Sc1=Sb1=7 and Sb0=5. FORC-Principal component analysis were also performed to all FORC data.